Dementia as social experience
1 online resource (234 pages)
Keywords: A diagnosis of dementia changes the ways people engage with each other – for those livingwith dementia, as well their families, caregivers, friends, health professionals, neighbours, shopkeepers and the community. Medical understandings, necessary as they are, provide no insights into how we may all live good lives with dementia.This innovative volume brings together an interdisciplinary group of researchers and practitioners to focus on dementia as lived experience. It foregrounds dementia’s social, moral, political and economic dimensions, investigating the challenges of reframing the dementia experience for all involved.? Part I critiques the stigmas, the negativity, language and fears often associated with a dementia diagnosis, challenging debilitating representations and examining ways to tackle these. Part II examines proactive practices that can support better long-term outcomes for those living with dementia. Part III looks at the relational aspects of dementia care, acknowledging and going beyond the notion of person-centred care. Collectively, these contributions highlight the social and relational change required to enhance life for those with dementia and those who care for them. Engaging in a critical conversation around personhood and social value, this book examines the wider social contexts within which dementia care takes place. It calls for social change, and looks for inspiration to the growing movement for relational care and the caring society. Dementia as Social Experience is important reading for all those people who, in various ways, are living with dementia, as well as for those working in this area as clinicians, researcher and carers.